DisCrit Literacies: Early Childhood Teachers Critically Reading School as Text and Imagining an Otherwise. Issue 4 (8th April 2022) - Beneke, Margaret R.; Machado, Emily; Taitingfong, Jordan
Abstract: In this participatory case study, we explored the critical literacy practices of early‐career early childhood teachers in a year‐long inquiry group, examining how they collectively read school as text through DisCrit literacies. Bridging literature from Disability Critical Race Theory (DisCrit) and critical literacies scholarship, DisCrit literacies involve practices of critically reading school itself as text and uncovering intersecting systems of ableism and racism. We describe teachers' collective engagement in DisCrit literacies, in which they: (a) deconstructed literacy practices and broader schooling mechanisms through repeated shared readings; (b) implicated themselves through critical readings of literacy classroom artifacts; and (c) identified and designed spaces of subversion and refusal in their literacy classrooms. Across each of these practices, early career early childhood teachers in our study used critical reading practices rooted in interdependence and presumptions of competence to redesign literacy routines. Ultimately, DisCrit literacies supported teachers in dismantling systems of regulation and classification in their early literacy classrooms, and—in solidarity with multiply‐marginalized children— imagining otherwise possibilities. We conclude with implications for teacher education and research, exploring how we might use DisCrit literacies to move toward humanizing early literacy spaces with and for multiply‐marginalized young children. Abstract : In this participatory case study, we explored the critical literacy practices of early‐career early childhood teachers in a year‐long inquiry group, examining how they collectively read school as text through DisCrit literacies. Bridging literature from Disability Critical Race Theory (DisCrit) and critical literacies scholarship, DisCrit literacies involve practices of critically reading school itself as text and uncovering intersecting systems of ableism and racism.